Efeito do inibidor de tirosina-quinase sunitinibe sobre a cicatrização alveolar pós-exodontia : estudo histomorfométrico - Ratzkowski, Bruna (2018)
Medication-related osteonecrosis of the jaw (MRONJ) is an important side effect that has been affecting patients undergoing different anticancer therapies, including antiangiogenic drugs. The aim of this study was to investigate the effect of tyrosine kinase inhibitor sunitinib on tissue repair at tooth extraction sites. Fifty-two Wistar rats were allocated into four groups according to the treatment received: (1) sunitinib (n=13); (2) sunitinib/zoledronic acid (n=13); (3) zoledronic acid (n=13); (4) control group (n=13). The animals were subjected to extractions of the right upper molars, and maxillae were dissected and macro- and microscopically analyzed. On macroscopic evaluation, the zoledronic acid group showed a significantly higher prevalence of oral mucosal lesion than the other groups; however, the size of this lesion did not significantly differ between groups. The sunitinib/zoledronic acid group had significantly less epithelium than the zoledronic acid and control group, but showed no significant difference compared to the sunitinib group. The other groups did not show any significant difference regarding this variable. The sunitinib/zoledronic acid and zoledronic acid groups did not differ from each other, but had significantly less connective tissue and more non-vital bone and microbial colonies than the sunitinib and control groups, whereas these latter two groups did not significantly differ from each other. Vital bone, inflammatory infiltrate and tooth fragment did not significantly differ between the groups. Conclusion: Sunitinib alone is not associated with non-vital bone, whereas the sunitinib/zoledronic acid combination and zoledronic acid alone are.